Perioperative use of enteral nutrition with ω-3 polyunsaturated fatty acid in patients with gastric cancer: a meta-analysis - Fu, Tingting; Hu, Wenjun; Chang, Lu; Duan, Jingli (Frontiers in Oncology, 2024)
ObjectivesTo systematically evaluate the efficacy and safety of enteral nutrition with ω-3 polyunsaturated fatty acid preparations or standard enteral nutrition preparations used in patients with gastric cancer during perioperative period, and to provide reference for clinical rational drug use.MethodsPubmed, EMbase, The Cochrane Library, CNKI and Wanfang Medical databases were searched by computer to collect relevant literature. The search period was from the establishment of the database to August 1, 2024. Meta-analysis was performed using Revman5.4 software after two researchers independently screened literature, extracted data, and evaluated the risk of bias in included studies.ResultsA total of 20 randomized controlled studies were included. The Meta results showed that there was no statistical difference in mortality between the enteral nutrition with ω-3 polyunsaturated fatty acid group and the control group (RR = 0.46, P = 0.17). However, the IEN group demonstrated superior advantages in reducing infection complications (RR = 0.81, P = 0.05) and wound infection (RR = 0.61, P = 0.04) among gastric cancer patients, as well as improving immune-related indicators (including IgG, IgA, IgM, CD4, and CD4/CD8), inflammation-related markers (including CRP, IL-1β, and IL-6), and nutritional indicators (including Total protein, Albumin, and Transferrin).Conclusionenteral nutrition with ω-3 polyunsaturated fatty acid preparation has advantages in the efficacy and safety of perioperative nutritional therapy in patients with gastric cancer, and can be used as a clinical choice. Due to the limited number and quality of included studies, the above conclusions need to be verified by more high-quality studies.